Uniform voltage distribution analysis for high peak voltage antenna tuner switch. Issue 5 (18th January 2021) - Ren, Jiangchuan; Dai, Ruofan; He, Jun; Zhang, Zhengxuan; Zou, Shichang
Abstract: This paper presents a theoretical analysis for achieving uniform voltage distribution among stacked field effect transistors (FETs) of RF tuner switch. The RF peak voltage ( V peak ) is limited by the unequal divided voltage drop among stacked FETs. A simplified equivalent capacitor circuit is established and an analytical expression is then derived for the first time to decide the value of ideal equivalent capacitance of each FET in the stack for achieving equal voltage division. Varying size of each stacked FET to set that the drain‐to‐source capacitance ( C ds ) equals to the capacitance from the proposed analytical expression can obtain a uniform voltage distribution, and thus a much higher V peak . To validate the proposed analytical expression, a 4‐shunt single‐pole single‐throw (4xSPST) switch is fabricated in HHGrace's 0.13 μm RF silicon‐on‐insulator process. Simulation and measurement results show that the switch features a uniform voltage distribution and a significant improvement in V peak .